Large contributions of petrogenic and aged soil-derived organic carbon to Arctic fjord sediments in Svalbard - Dahae Kim; Jung-Hyun Kim; Youngkyu Ahn; Kwangchul Jang; Ji Young Jung; Minji Bae; Seung-Il Nam (Scientific Reports, 2023)
Abstract Svalbard fjords are recognized as hotspots for organic carbon (OC) burial and storage due to their high sedimentation rates, which effectively trap terrestrial sediments and inhibit extensive OC remineralization. In this study, we investigated surface sediments (n = 48) from eight Svalbard fjords, along with bedrock (n = 17), soil (n = 28), and plant (n = 12) samples, to identify the sources of sedimentary OC in these fjords using geochemical parameters. All examined surface sediments from the fjords showed a depletion in 14Corg (− 666.9 ± 240.3‰), indicating that recently fixed terrestrial and marine biomass alone cannot account for the entire sedimentary OC pool. Conventional bulk indicators such as Norg/TOC ratio and δ13Corg were insufficient for fully determining the sources of sedimentary OC. Therefore, we employed a four-end-member approach, using Δ14Corg, δ13Corg, and lignin phenols to assess the relative contributions of petrogenic, soil-derived, plant-derived, and marine OC to the sedimentary OC pool. The analyzed fjord sediments consisted, on average, of 59.0 ± 28.1% petrogenic OC, 16.8 ± 12.1% soil-derived OC, 2.5 ± 2.2% plant-derived OC, and 21.8 ± 18.5% marine OC. This approach highlights the substantial contributions of petrogenic and aged soil-derived OC to present-day sedimentary OC in Svalbard fjords. Considering predicted global warming, accelerated inputs of petrogenic and soil-derived OC into fjords due to rapid glacier retreat may significantly impact the active carbon cycle and potentially contribute to CO2 emissions to the atmosphere, depending on burial efficiency.